GAMBARAN PENYELENGGARAAN PELAYANAN KB BERGERAK DI WILAYAH PERBATASAN DAN KEPULAUAN PADA TAHUN 2019 - Lidya Dwijayani (Jurnal Informasi Kesehatan Indonesia (JIKI), 2021)
Abstract Background: The low level of participation in family planning in border areas and archipelago, has made the government, in this case, BKKBN, do an innovative liked mobile family planning service. The achievement of family planning participation is influenced by various factors. Method: This study used a descriptive design with a cross-sectional approach. Result: There are 34 (100%) provinces that have provided mobile family planning services, 33 (97,1%) provinces have provided mobile family planning services in border areas, 20 (60,6%) provinces have also implemented its services in the archipelago. 31 (91,2%) provinces use health facilities as a means of providing mobile family planning services, 33 (97,1%) provinces use MUYAN KB. 23 (67,6%) provinces have involved partners from FKRTL, 34 (100%) involved TNI, and 28 (82,4%) involved partners from FKTP. Discussion: Fulfilling the accessibility of contraceptives and reproductive health services in border areas and the archipelago is influenced by various factors, including the availability of health facilities and supporting facilities, easy access, availability of medicines, medical devices and disposables, availability of health personnel resources, cross-sector partnerships and mechanism integrated reference patterns. Conclusion: Fulfilling the factors that affect the accessibility of quality contraceptive and reproductive health services in border areas and islands requires the collaboration of various parties. Keywords: mobile family planning, border areas, the archipelago